HUBUNGAN ANTARA DUKUNGAN SOSIAL DENGAN KECEMASAN MENGHADAPI UJIAN NASIONAL PADA SISWA SMA NEGERI 2 KOTA MAGELANG - Fiona Fisabillia Lastina; Zaenal Abidin (Jurnal EMPATI, 2013)
The purpose of the research is to know correlation between the social support and the test anxiety on senior high school student at SMA Negeri 2, Magelang. Hypothesis of this study expressed that there is a negative correlation between the social support  and the test anxiety on the senior high school students  at SMA Negeri 2, Magelang. The more positive social support  the lower levels of test anxiety in the senior high school students  at SMA Negeri 2, Magelang.The instruments of this study used Social Support Scale text anxiety Scale. Social Support  Scale consists of 38 items with difference indices of items ranged of 0.332 to 0.639 and a reliability coefficient of 0.913. Test Anxiety Scale consists of 31 items with a difference indices of items ranged of 0.307 to 0.846 and reliability coefficient of 0.940.Population in this study was 200 senior high school students at SMA Negeri 2, Magelang. The samples were amounted 100 students and sampled by using cluster random sampling technique. Analysis of the data carried out by using simple regression analysis with the correlation coefficient (rxy) of -0.581 with p = 0.000 (p <0.05), it means that the hypothesis stated that there is a negative correlation between academic self-concept and academic procrastination was accepted.Contribution of social support on the test anxiety in the senior high school students at SMA Negeri 2, Magelang is 33.80%. While the remaining of 66.20% is influenced by other factors that are not discussed in this study.